Body Movement Is Associated With Orgasm During Vaginal Intercourse in Women. Issue 3 (24th March 2019) - Bischof-Campbell, Annette; Hilpert, Peter; Burri, Andrea; Bischof, Karoline
Abstract : Very few studies have investigated the relationship between women's ability to experience an orgasm during vaginal intercourse and specific stimulation techniques. We examined two common techniques during vaginal intercourse both with and without simultaneous external clitoral stimulation: (1) body movement, in particular back-and-forth swinging movements of the pelvis and trunk; and (2) precise rubbing of the clitoris with an immobilized body. Structural equation modeling was used to compare the effects of the two stimulation techniques on women's orgasm frequency ( N  = 1, 239). As hypothesized, the frequency of orgasm during vaginal intercourse with simultaneous clitoral stimulation was positively associated with a preference for body movement during arousal. Body movement, as opposed to body immobilization, was also associated with a higher frequency of orgasm during vaginal intercourse without simultaneous clitoral stimulation. We conclude that body movement is associated with more orgasms during vaginal intercourse, whereas precise rubbing of the clitoris with an immobilized body is not associated with more orgasms. Teaching women to move their pelvis and trunk in a swinging back-and-forth movement during vaginal intercourse might therefore facilitate reaching an orgasm, whereas encouraging them to self-stimulate the clitoris might be less helpful if done with an immobilized body.